Corticosteroid-Induced Regression of Glioblastoma: A Radiographic Conundrum - Joshua A. Cuoco; Joshua A. Cuoco; Joshua A. Cuoco; Joshua A. Cuoco; Brendan J. Klein; Brendan J. Klein; Brendan J. Klein; Brendan J. Klein; Christopher M. Busch; Christopher M. Busch; Christopher M. Busch; Christopher M. Busch; et al. (Frontiers in Oncology, 2019)
Corticosteroid-induced regression of lesion contrast enhancement on imaging studies is most commonly appreciated with primary central nervous system lymphoma; however, although exceedingly rare, a limited number of primary and metastatic intracranial lesions have been reported to exhibit similar radiographic changes subsequent to corticosteroid therapy. To date, there have been six cases of glioblastoma reported to exhibit such changes. Lesion transformation on repeat imaging after the initiation of steroids represents a diagnostic dilemma for clinicians when attempting to differentiate between a diagnosis of glioblastoma and lymphoma. Stereotactic biopsy may be inadvertently postponed due to high clinical suspicion for steroid-induced cytotoxicity traditionally seen with lymphomatous cells. To highlight this radiographic conundrum, we present a rare case of corticosteroid-induced regression of glioblastoma and discuss the relevant literature. To our knowledge, this is the first case report to describe the molecular profile of a glioblastoma that underwent corticosteroid-induced regression.